The Kinetics of Mesophyll Conductance and Photorespiration During Light Induction - Ningyu Liu; Jianxin Cao; Mingying Yang; Yiyun Li; Wei Huang (Plants)
Mesophyll conductance to CO2 (gm) act as a significant limiting factor influencing the CO2 assimilation rate (AN) during photosynthetic induction. However, the effect of vapor pressure deficit (VPD) on gm kinetics during light induction is not well clarified. We combined gas exchange with chlorophyll fluorescence measurements to assess the induction kinetics of gm during light induction under contrasting vapor pressure deficit (VPD) in two tree species with different stomatal conductance (gs) behavior, Catalpa fargesii and Pterocarya stenoptera. Our results revealed three key findings: (1) the coordination of gm and gs kinetics during light induction occurred in C. fargesii but not in P. stenoptera, and the model of gs kinetics largely determines whether the coordination of gs and gm exist in a given species; (2) a high VPD induced simultaneous changes in gs and gm kinetics in C. fargesii but had separated effects on gs and gm kinetics in P. stenoptera, indicating that the response of gm kinetics during light induction to VPD differs between species; and (3) the relative contribution of photorespiration to total electron flow was flexible in response to the change in relative diffusional and biochemical limitations, pointing out that photorespiration has a significant role in the regulation of photosynthetic electron flow during light induction. These results provide new sight into the species-dependent kinetics of gm and photorespiration during light induction.